bc(b-c)+ca(c-a)+ab(a-b)因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:23:54
bc(b-c)+ca(c-a)+ab(a-b)因式分解bc(b-c)+ca(c-a)+ab(a-b)因式分解bc(b-c)+ca(c-a)+ab(a-b)因式分解bc(b-c)+ca(c-a)+ab(
bc(b-c)+ca(c-a)+ab(a-b)因式分解
bc(b-c)+ca(c-a)+ab(a-b)因式分解
bc(b-c)+ca(c-a)+ab(a-b)因式分解
bc(b-c)+ca(c-a)+ab(a-b)
=b^2c-bc^2+ac^2-a^2c+a^2b-ab^2
=(b^2c-a^2c)-(bc^2-ac^2)-(-a^2b+ab^2)
=c(b^2-a^2)-(b-a)c^2-ab(b-a)
=c(b+a)(b-a)-(b-a)c^2-ab(b-a)
=(b-a)(bc-ac-c^2-ab)
bc(b-c)+ca(c-a)+ab(a-b)
=bc(b-c)+cca-caa+aab-abb
=bc(b-c)+(cca-abb)+(aab-aac)
=bc(b-c)+a(c-b)(c+b)+aa(b-c)
=(b-c)[bc-a(c+b)+aa]
=(b-c)[bc-ac-ab+aa]
=(b-c)[b(c-a)-a(c-a)]
=(b-c)(c-a)(b-a)
计算:c/ab+a/bc+b/ca,
计算:c/ab + a/bc + b/ca
bc(b-c)+ca(c-a)+ab(a-b)因式分解
因式分解:ab*b+c*c+ca*a+a*ab+b*bc+c*ca+2abc
bc(b+c)+ca(c-a)-ab(a+b)因式分解bc(b+c)+ca(c-a)-ab(a+b)=bc(c-a+a+b)+ca(c-a)-ab(a+b) =bc(c-a)+bc(a+b)+ca(c-a)-ab(a+b)=bc(c-a)+ca(c-a)+bc(a+b)-ab(a+b) =(bc+ca)(c-a)+(bc-ab)(a+b)=c(c-a)(b+a)+b(a+b)(c-a) =(c+b)(c-a)(a+b).(bc+ca)(c-a)+(bc-ab)(a+b)是
如何证明(a+b+c)(ab+bc+ca)-abc=(a+b)(b+c)(c+a)
已知非零有理数a、b、c,求ab/ |ab|+bc/|bc|+ca/|ca|+abc/|abc|
已知a.>b>c求证ab+bc+ca>ab+bc+ca
a+b+c=0证明ab+bc+ca
因式分解abc+ab+bc+ca+a+b+c+1=
a²+b²+c²-ab-bc-ca因式分解
因式分解a^2+b^2+c^2-ab-bc-ca
a>b>c,bc^2+ca^2+ab^2
分解因式:(a+b+c)(ab+bc+ca)+abc
√(a/bc)+√(b/ca)√(c/ab)
已知a+b+c=0,求证:ab+bc+ca
a方+b方+c方-ab-bc-ca=?
a+b+c=0 求证ab+bc+ca